2010
DOI: 10.1007/s10646-010-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of the herbicide glufosinate ammonium on crops and wild plants: short-term effects compared to vegetative recovery and plant reproduction

Abstract: Current guidelines for phytotoxicity testing rely heavily on short-term testing of primarily crop species to predict the sensitivity of non-target, wild plants to herbicides. However, little is known on how plants recover following initial growth inhibitions in standard 14-28 day greenhouse tests conducted for pesticide assessment and registration. The objectives of this study were to assess the ability of plant species to recover (biomass and reproduction) when tested at the juvenile stage (routine regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…In addition, an NOED of 0.058 g a.i./ha was found in weeks 6 and 7, while an NOED of 0.348 g a.i./ha was found in week 8. This difference suggests that plants can recover from spraying, as was also found in other studies (de Snoo et al, 2005;Carpenter and Boutin, 2010;Strandberg et al, 2012;Schmitz et al, 2014). In comparison with lower-level treatments, plots with dosages of 0.174 and 0.348 g a.i./ha featured more grasses (Poaceae), as we found through visual observation.…”
Section: Discussion Of Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, an NOED of 0.058 g a.i./ha was found in weeks 6 and 7, while an NOED of 0.348 g a.i./ha was found in week 8. This difference suggests that plants can recover from spraying, as was also found in other studies (de Snoo et al, 2005;Carpenter and Boutin, 2010;Strandberg et al, 2012;Schmitz et al, 2014). In comparison with lower-level treatments, plots with dosages of 0.174 and 0.348 g a.i./ha featured more grasses (Poaceae), as we found through visual observation.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…The lack of statistical differences can be explained by the low number of observations, which also varied between the plots, reducing the power of the statistical tests. Other studies have demonstrated that reproductive endpoints are indeed very sensitive to metsulfuron-methyl Blackburn and Boutin, 2003;Olszyk et al, 2004;Kjaer et al, 2006;Carpenter and Boutin, 2010;Pfleeger et al, 2012;Schmitz et al, 2014Schmitz et al, , 2015. Our results also showed hormesis occurring in S. alba, P. tanacetifolia and C. cyanus, at low dosages of metsulfuron-methyl and in both vegetative and reproductive endpoints.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies could show that seed production is often more reduced by herbicides compared to weed biomass [24,25,26,27]. The presented results suggest that this is only true for A. fatua under high crop competition.…”
Section: Discussionmentioning
confidence: 69%
“…Species related to the crops for which a specific herbicide is intended for use usually have a higher tolerance to that herbicide (White and Boutin, 2007). Several studies conducted in Canada and Denmark have shown that there is no significant difference between the sensitivity of short-and long-lived species (Boutin et al, 2004;Carpenter and Boutin, 2010;Strandberg et al, 2012). Therefore, it is not possible at this stage to propose one species which is generally more sensitive to toxicants.…”
Section: Non-target Terrestrial Plantsmentioning
confidence: 99%